2004
DOI: 10.1590/s0103-90162004000400010
|View full text |Cite
|
Sign up to set email alerts
|

Aggressiveness and physiological specialization of Septoria tritici Rob. isolates

Abstract: Pathogenicity tests verifying the behavior of Septoria tritici isolates should be considered as a priority in the selection of resistant wheat materials to this pathogen, since the aggressiveness of each isolate can vary significantly, causing problems in the evaluation and selection of resistant genotypes. The objective of this work was to determine whether physiologic specialization exists among Argentinean and American Septoria tritici isolates, through the analysis of their pathogenicity on cultivars and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…The cultivars differed in plant height, heading date, and resistance to Septoria tritici blotch, and represented the range in these characteristics for cultivars grown in Argentina in 1998. ‘Klein Toledo’, an old cultivar, also was included because it is moderately resistant to Septoria tritici blotch (Gieco et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The cultivars differed in plant height, heading date, and resistance to Septoria tritici blotch, and represented the range in these characteristics for cultivars grown in Argentina in 1998. ‘Klein Toledo’, an old cultivar, also was included because it is moderately resistant to Septoria tritici blotch (Gieco et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Pathogenicity assays showed the action of Zt isolates should be regarded as a priority in the selection of resistant wheat materials to this disease (Brian 1976; Ghaffary 2011). Therefore, several studies have indicated that different wheat genotypes interact differently with different Zt isolates, indicating that the pathogen has physiological speci city (Ababa et al 2022;Ballantyne 1989;Boughalleb and Harrabi 1997;Brading et al 2002;Brian 1976; Dalvand et al 2018;Ghaffary 2011;Gieco et al 2004;Grieger 2001;Hosseinnezhad et al 2014;Jlibene et al 1993; Kema et al 1995;Kema and Vansilfhout 1997;Makhdoomi et al 2015;Mekonnen et al 2020;Saadaoui 1987). Hence, understanding the population diversity and pathogen virulence pattern is critical for developing the most effective and long-lasting resistance breeding strategies (Brading et al 2002;Dalvand et al 2018;Ghaffary 2011;Grieger 2001; Gri ths and Ao 1980; Makhdoomi et al 2015).…”
Section: )mentioning
confidence: 99%
“…El primer marcador usado para Septoria tritici en Argentina fue la virulencia Cordo & Arriaga, 1990;Perelló et al, 1990a y b;Giecco et al, 2004). Sin embargo, la virulencia en este hongo es un carácter muy sensible a las condiciones ambientales, originando dificultades en la evaluación (Cordo et al, 2006).…”
Section: Marcadores Moleculares Y Su Aplicación Al Control De La Enfe...unclassified